Priority setting for new technologies in medicine: qualitative case study. Issue 7272 (25th November 2000) - Singer, Peter A; Martin, Douglas K; Giacomini, Mita; Purdy, Laura
Abstract: Objective: To describe priority setting for new technologies in medicine. Design: Qualitative study using case studies and grounded theory. Setting: Two committees advising on priorities for new technologies in cancer and cardiac care in Ontario, Canada. Participants: The two committees and their 26 members. Main outcome measures: Accounts of priority setting decision making gathered by reviewing documents, interviewing members, and observing meetings. Results: Six interrelated domains were identified for priority setting for new technologies in medicine: the institutions in which the decision are made, the people who make the decisions, the factors they consider, the reasons for the decisions, the process of decision making, and the appeals mechanism for challenging the decisions. Conclusion: These domains constitute a model of priority setting for new technologies in medicine. The next step will be to harmonise this description of how priority setting decisions are made with ethical accounts of how they should be made.